Autoreactivity and broad neutralization of antibodies against HIV-1 are governed by distinct mutations: Implications for vaccine design strategies - Li, Xiaojun; Liao, Dongmei; Li, Zhengyang; Li, Jixi; Diaz, Marilyn; Verkoczy, Laurent; Gao, Feng (Frontiers in Immunology, 2022)
Many of the best HIV-1 broadly neutralizing antibodies (bnAbs) known have poly-/autoreactive features that disfavor normal B cell development and maturation, posing a major hurdle in developing an effective HIV-1 vaccine. Key to resolving this problem is to understand if, and to what extent, neutralization breadth-conferring mutations acquired by bnAbs contribute to their autoreactivity. Here, we back-mutated all known changes made by a prototype CD4 binding site-directed bnAb lineage, CH103-106, during its later maturation steps. Strikingly, of 29 mutations examined, only four were crucial for increased autoreactivity, with minimal or no impact on neutralization. Furthermore, three of these residues were clustered in the heavy chain complementarity-determining region 2 (HCDR2). Our results demonstrate that broad neutralization activity and autoreactivity in the CH103-106 bnAb lineage can be governed by a few, distinct mutations during maturation. This provides strong rationale for developing immunogens that favor bnAb lineages bearing “neutralization-only” mutations into current HIV-1 vaccine designs.